2020
DOI: 10.31285/agro.24.112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the agronomic interest characteristics for the management of Conyza blakei, Conyza bonariensis, Conyza sumatrensis, and Conyza lorentzii

Abstract: Conyza genus includes herbs of ruderal habit, also referred to weeds in pastures, perennial crops, and no tillage crops. The insuitable use of herbicides, the incorrect identification of species, and the lack of monitoring, among others, explain the fact that Conyza species have become a growing problem in production systems under no tillage. Therefore, the knowledge of biology and the adaptive response to diverse cultural practices is paramount. Two of the most important characteristics to establish managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These traits suggest that the sole reliance on glyphosate for tall fleabane control in fallows and glyphosate-resistant cotton crops in Australia may result in a rapid increase in resistant cases. Tall fleabane is a self-pollinated species, and wind-mediated dispersal of seeds could help in the spread of resistance from one field to another (Andersen 1993;Diez de Ulzurrun et al 2020;Hao et al 2009). A study in China concluded that autonomous seed production contributed significantly to the invasiveness of tall fleabane (Hao et al 2009).…”
Section: Experiments 1 Glyphosate Dose Responsementioning
confidence: 99%
See 1 more Smart Citation
“…These traits suggest that the sole reliance on glyphosate for tall fleabane control in fallows and glyphosate-resistant cotton crops in Australia may result in a rapid increase in resistant cases. Tall fleabane is a self-pollinated species, and wind-mediated dispersal of seeds could help in the spread of resistance from one field to another (Andersen 1993;Diez de Ulzurrun et al 2020;Hao et al 2009). A study in China concluded that autonomous seed production contributed significantly to the invasiveness of tall fleabane (Hao et al 2009).…”
Section: Experiments 1 Glyphosate Dose Responsementioning
confidence: 99%
“…In Australia, tall fleabane is present in all the states and territories, except the Northern Territory (AVH 2022). In addition to infesting fallow fields, it is a problematic weed in cotton (Gossypium hirsutum L.) and horticultural fields (Diez de Ulzurrun et al 2020;Everett 1990;Thebaud and Abbott 1995) in other countries.…”
Section: Introductionmentioning
confidence: 99%